Analisis Pengaruh Jam Kerja, Jumlah Pembeli, dan Modal Usaha terhadap Pendapatan Usaha Warung Kopi (Studi Kasus pada Pedagang Usaha Warung Kopi di Kecamatan Benowo, Surabaya Barat) - Rosita Widyawati; Pratiwi Dwi Karjati (Faculty of Economic an Business Wijaya Kusuma Surabaya University, 2021)
This study aims to determine the effect of working hours, amount buyers, and startup capital for income of coffee shop seller in sub-district of Benowo. This research uses quantitative research with descriptive approach. Data used in this research is a Cross Section, by using the slovin formula a sampel of 126 respondents was obtain. Method of data collection by questionnaire. Technique of data analys used is a multiple linear regression methods with program eviews. Based on the partial test by level of significance (α = 5%), working hours have a possitive effect and significance for incomers seller with a probability value 0.0103, amount of buyers have a possitive effect and significance for incomers seller with probability 0.0002, startup capital is so have a possitive effect and significance for income seller with probability 0.0016. Based on simultan test, result of research design showed that working hours, amount buyers and startup capital can give significance effect for income coffee shop seller in sub-district of Benowo. All about that can be showed by probability value F-statistic is a 0.0000.